Making meaning: reflections on the act of teaching in prison. Issue 1 (2nd January 2019) - Novek, Eleanor
ABSTRACT: Prison educators "stand at the crossroads of liberation and incarceration." They promote education, which can be a tool of personal freedom, in a setting designed to oppress and control. What practices help them accomplish the objectives of liberatory learning? This essay traces the philosophical and relational premises that I believe are essential for educators teaching in prisons. It begins with a basic characterization of prison education in contemporary settings. The essay then examines the pedagogies of several prison educators who, despite their different disciplines and perspectives, emphasize the importance of identity, relational dynamics, and participatory learning. Finally, the essay offers recommendations for thinking through a learner-centered approach to pedagogical design that can help incarcerated students better understand their lives and claim their voices under oppressive conditions.